(untitled) (Al-Qamar, 2025)
Eminᾱbᾱd is one of the historical towns of Punjab which is the land of five rivers. It is located near Gujrᾱnwᾱla district. Gujrᾱnwᾱla is a division in the Punjab Province of Pakistan. Eminᾱbᾱd is one of the most representative urban areas of medieval Punjab and has all the significant features such as urban structure and form, domestic architecture and architecturally and culturally valuable sites and historic monuments which coexist with traditional cultural heritage. Eminabad has lost all its glory but even now has much more to offer its visitors. In spite of the damage the town has a personality of its own which has not so far been highlighted before.